2015
DOI: 10.1074/jbc.m114.602789
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Insulin Signaling in Mouse Hepatocytes Is Associated with Increased Phosphatidic Acid but Not Diacylglycerol

Abstract: Background:The mechanism underlying the association of triacylglycerol storage and insulin resistance is unclear. Results: Increasing phosphatidic acid (PA) in primary hepatocytes via de novo synthesis or action of phospholipase D or diacylglycerol kinase-disrupts insulin signaling. Conclusion: PA derived from different sources inhibits insulin signaling. Significance: Increases in hepatocyte PA may mechanistically link lipid storage and insulin action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
15
2
Order By: Relevance
“…In contrast to the lack of differences in PA levels observed in our deficiency model, the overexpression of Pld1 in a whole cell system increases the total PA level39. Elevated PA levels in Pld1 -overexpressing hepatocytes inhibit Akt by disrupting mTORC239, which localizes to the plasma membrane40. Based on the different localization patterns of mTORC2 and PLD1, the lysosomal deficiency of PA probably does not regulate insulin-stimulated Akt via mTORC2.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast to the lack of differences in PA levels observed in our deficiency model, the overexpression of Pld1 in a whole cell system increases the total PA level39. Elevated PA levels in Pld1 -overexpressing hepatocytes inhibit Akt by disrupting mTORC239, which localizes to the plasma membrane40. Based on the different localization patterns of mTORC2 and PLD1, the lysosomal deficiency of PA probably does not regulate insulin-stimulated Akt via mTORC2.…”
Section: Discussioncontrasting
confidence: 57%
“…Indeed, other PA-generating enzymes, such as GPAT/AGPAT and DGK, are localized on the endoplasmic reticulum and mitochondrial membranes37 and are unlikely to regulate the lysosomal PA level. In contrast to the lack of differences in PA levels observed in our deficiency model, the overexpression of Pld1 in a whole cell system increases the total PA level39. Elevated PA levels in Pld1 -overexpressing hepatocytes inhibit Akt by disrupting mTORC239, which localizes to the plasma membrane40.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, DGKθ is highly expressed in the cerebellum and hippocampus in the adult rat brain . Furthermore, overexpression of DGKθ mainly increased the amount of 18:1/18:1‐PA in mouse primary hepatocytes . Therefore, these results imply that the abnormal aggregation of the α‐syn protein results from 18:1/18:1‐PA production by DGKθ in the brain.…”
Section: Discussionmentioning
confidence: 80%
“…We detected that hepatocytes and 3T3 fibroblasts accumulate fully saturated PAs in response to SCD inhibition. Interestingly, recent studies have demonstrated that hepatic fully saturated PAs such as 16:0/16:0-PA, but not unsaturated PAs derived from de novo glycerolipid synthesis, inhibit the mTOR complex 2, leading to insulin resistance (60,61). Therefore, fully saturated PAs may not only play a critical role in vascular calcification, but also in many other cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%